DIKLAT BERBASIS PROYEK MENDORONG KREATIVITAS DAN INOVASI DI ERA MODERN - Abdul Rumkel; Moch. Nur Syawalludin Nugroho; Hartinah (Program Studi Manajemen Pendidikan Islam, 2026)
The development of modern education requires learning strategies that can encourage creativity, innovation, and practical skills among students. However, in Frontier, Outermost, and Disadvantaged (3T) areas such as Sorong Regency, limitations in educational infrastructure, access to technology, and availability of educators remain challenges to improving the quality of learning. This study aims to analyze the role of project-based training in promoting creativity and innovation in education in 3T areas. The study uses a literature review approach with qualitative descriptive analysis techniques through the examination of various scientific literature relevant to project-based learning. The results of the study show that project-based training can improve critical thinking skills, creativity, and the collaborative abilities of students through contextual learning activities based on real-world problem solving. This approach also has the potential to support the development of practical skills relevant to the needs of local communities and contribute to improving the quality of human resources in the region.